2014
DOI: 10.3109/17435390.2014.976851
|View full text |Cite
|
Sign up to set email alerts
|

Both released silver ions and particulate Ag contribute to the toxicity of AgNPs to earthwormEisenia fetida

Abstract: To disentangle the contribution of ionic and nanoparticulate Ag to the overall toxicity to the earthworm Eisenia fetida, a semi-permeable membrane strategy was used to separate Ag + released from silver nanoparticles (AgNPs) in an aqueous exposure. Internal Ag fractionation, activities of antioxidant enzymes and metabolites in E. fetida were determined after 96 h of exposure to two sizes of polyvinylpyrrolidone-coated AgNPs. The response of the antioxidant system combined with the content of malondialdehyde in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 45 publications
(55 reference statements)
3
23
0
2
Order By: Relevance
“…Conversely, no ketones were found at all the Ag surfaces, and no surface C=O groups have been revealed with in situ SERS for the iron-free media too [9,10], probably because of stabilization of alcohol group bound to silver. Li et al [10] have interpreted the SERS spectra by a silver impact [43,44] implying that AgNPs may disturb the biochemical enzymatic oxidation of citrate by stabilizing the alcohol group as one of the mechanisms of silver toxicity.…”
Section: Origin Of the Citrate-derived Ligandsmentioning
confidence: 99%
“…Conversely, no ketones were found at all the Ag surfaces, and no surface C=O groups have been revealed with in situ SERS for the iron-free media too [9,10], probably because of stabilization of alcohol group bound to silver. Li et al [10] have interpreted the SERS spectra by a silver impact [43,44] implying that AgNPs may disturb the biochemical enzymatic oxidation of citrate by stabilizing the alcohol group as one of the mechanisms of silver toxicity.…”
Section: Origin Of the Citrate-derived Ligandsmentioning
confidence: 99%
“…However, Qian et al (2013) compared the toxicity of silver nanoparticles and silver ions on the growth of terrestrial plant model Arabidopsis thaliana and found that Ag NPs showed stronger toxicity to A. Thaliana compared with Ag þ , demonstrating that growth inhibition and cell damage of plants can be directly attributed to the nanoparticles themselves, not only the dissolved silver released from Ag NPs. And other authors reported that both silver ions and Ag NPs contribute to the toxicity (Kawata et al, 2009;Li et al, 2015;Navarro et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In the oysters from BJ, choline and phosphocholine were significantly elevated, which suggested that this reaction was enhanced in oysters. Li et al (2015) reported that the phosphocholine was also elevated in Ag + -exposed Eisenia fetida. Since the oysters from BJ site accumulated the highest concentration of Ag, the elevation of phosphocholine might be the metabolic biomarker of Ag.…”
Section: Metal/metalloid Concentration (μG/g Dw) Amentioning
confidence: 98%